ASEAN REFORM: TOWARDS A MORE COHESIVE REGIONAL INTERGOVERNMENTAL ORGANISATION - Yogi Bratajaya (Padjadjaran Journal of International Law, 2019)
AbstractThe Association of Southeast Asian Nations (ASEAN) is a regional intergovernmental organization that has seen exponential growth throughout the course of its lifespan ever since it was founded in August 8 of 1967. The organization comprises of 10 Member States with differing backgrounds in economy, culture and government. Its aims and purposes include “To promote regional peace and stability through abiding respect for justice and the rule of law in the relationship among countries of the region and adherence to the principles of the United Nations Charter” based on the “Mutual respect for the interdependence, sovereignty, equality, territorial integrity, and national identity of all nations.” However, it seems that ASEAN’s fundamental principles are its main detriment to achieving and carrying out its aims and purposes. The organization has faced multiple criticisms regarding its failure to address pressing matters in the region, such as ongoing human rights violations committed by member states. The slowness in addressing these matters is due to its fundamental principles of non-intervention and mutual respect for political independence, which in turn causes the lack of comprehensive dispute settlement mechanisms within the organization. This journal aims to pinpoint and identify the root of the aforementioned problems and seeks to provide a comprehensive solution with reference to other regional organizations. Keywords: ASEAN, Legal Personality, Dispute Settlement, Human Rights AbstrakAssociation of SouthEast Asian Nations (ASEAN) merupakan sebuah organisasi antarnegara regional yang mengalami perkembangan pesat sejak terbentuknya pada 8 Agustus 1967. Saat sekarang ASEAN mengandung 10 anggota negara yang mempunyai latar-belakang ekonomi, budaya, dan sistem pemerintahan yang berbeda. Tujuan dari ASEAN adalah “To promote regional peace and stability through abiding respect for justice and the rule of law in the relationship among countries of the region and adherence to the principles of the United Nations Charter” berdasarkan “Mutual respect for the interdependence, sovereignty, equality, territorial integrity, and national identity of all nations.” Namun, prinsip dasar ASEAN seakan-akan menghambat ASEAN untuk mencapai tujuannya. Kritik yang dihadapi oleh ASEAN meliputi statusnya dalam hukum internasional, kurangnya efektivitas sistem penyelesaian sengketa di dalam ASEAN, dan bagaimana ASEAN mengatasi permasalahan Hak Asasi Manusia. Jurnal ini bertujuan untuk mengidentifikasi masalah tersebut dan memberi solusi komprehensif dengan meninjau kepada organisasi regional lain. Kata Kunci: ASEAN, Personalitas Hukum, Penyelesaian Sengketa, Hak Asasi Manusia